PEMBARUAN HUKUM TERHADAP LEMBAGA PRAPERADILAN MELALUI PUTUSAN PENGADILAN - Maskur Hidayat (Yuridika, 2015)
Law enforcement process is an effort to maintain security and public tranquility. The process of implementation of the law enforcement needs to be implemented correctly and legally. It is necessary to be controlled so that the process is not being done arbitrarily since the individual rights in the process of law enforcement have to be protected. Pre-trial is an institution that allows the monitoring of the actions done by the law enforcement agencies.Pretrial institutions are a form of mechanism provided by the state that can be used for any individual who feels that his rights have been arbitrarily deprived. Because basically protection of the individual is a goal and not just a tool. This means that there are limitations or side effects for an act that is allowed to disrupt fundamental human rights. Obtain a fair and open mechanism then the testing of state instrument actions in the form of deprivation of the right to liberty or confiscation of goods, such as the act of arrest, detention, determination of suspects, and seizure are placed in pretrial concepts held in open trials. With the hearing open, then the implementation of the trial other than built on the accountability of mutual supervision conducted by the parties there will also be supervision by those present in the open trial, such as community and mass media.